Classic and New Diagnostic Approaches to Childhood Tuberculosis - Gladys Guadalupe López Ávalos; Ernesto Prado Montes de Oca (Journal of Tropical Medicine)
Tuberculosis in childhood differs from the adult clinical form and even has been suggested that it is a different disease due to its differential signs. However, prevention, diagnostics, and therapeutic efforts have been biased toward adult clinical care. Sensibility and specificity of new diagnostic approaches as GeneXpert, electronic nose (E-nose), infrared spectroscopy, accelerated mycobacterial growth induced by magnetism, and flow lateral devices in children populations are needed. Adequate and timely assessment of tuberculosis infection in childhood could diminish epidemiological burden because underdiagnosed pediatric patients can evolve to an active state and have the potential to disseminate the etiological agent Mycobacterium tuberculosis, notably increasing this worldwide public health problem.